Effect of high pressure in barium disilicate glass investigated by DTA and Raman spectroscopy - Evaristo, Leonardo; Silveira, Rafael; Tissot, Matheus; Hippler, Gisele; Moulton, Benjamin; Buchner, Silvio (International Journal of Applied Glass Science, 2022)
This work aimed to explore the effect of high pressures at room temperature on the vibrational modes and the thermal properties and stability of barium disilicate glass (BaO-2SiO(2)) (BS2). The BS2 was prepared through the conventional melting route at atmospheric pressure. After being submitted to different pressure values (2.5 GPa, 4.0 GPa, and 7.7 GPa) and room temperature, the samples were characterized ex situ by Raman spectroscopy and differential thermal analysis. With this, it is possible to see that the pressure modifies the Raman vibrational modes of the glass, in the region associated with the Si-O-Si symmetrical bending modes. The Si-O symmetrical stretching vibrational modes (Q(n)) remain unchanged, however there are changes on values of glass transition and decrease crystallization temperature, as well as the parameters of thermal stability of the glass.
CRIS-Team WoS Importer:2022-09-02